Polimorfisme Gen Aquaporin-3 dan Pengaruhnya Terhadap Ikatan dengan Ligand Uji Secara In Silico - Sofyan, Hamny; Zakiah, Noni; Hasriati, Hasriati; Frengki, Frengki; Hidayat, Taufan; Aisyah, Siti (Jurnal Veteriner; Vol 23 No 2 (2022)DO - 10.19087/jveteriner.2022.23.2.157, 2022)
Changes in the genetic code can trigger changes in the function of the proteins it produces. Genetic changes that commonly occur in the form of single nucleotide polymorphism such as in the aquaporin group gene (AQPs) which play an important role in maintaining moisture and elasticity of the skin epidermis. This study aims to analyze the effect of mutations in one of the aquaporin protein groups (AQPs), namely aquaporin 3 (AQP3) by in silico. Research material in the form of data sequences and 3D structures of AQP3 wild-type dan AQP3 mutant downloaded from the protein databank (pdb id 1FX8 and 1LDF). These two sequences were aligned using the “ClustalW” method to observe the position of the mutation, while the 3D structures were also aligned using the “Alignment” method to observe changes in the native ligand’s “site binding” region. The impact of the conformational changes of mutant AQP3 was also observed on several compounds as test ligands which are known to work to support the function of AQP3 protein such as asiatic acid, madecassic acid, asiaticoside, and alpha-retinoic acid through molecular docking method. Sequence alignment results showed that mutations occurred in the 48th (tryptophan-phenylalanine) and 200th (phenylalanine-threonine) residue sequences. The mutation of the two residues caused a change in the interaction model of all test ligands compared to the normal type of AQP3. The mutation also causes a decrease in the stability of AQP3, but on the contrary does not change the function of AQP3 but only decreases the binding ability of the native ligand molecule which has implications for the decrease in the binding ability of water molecules, glycerol and the test ligand.